Development of an Augmented Reality Game to Teach Abstract Concepts in Food Chemistry. Issue 1 (January 2015) - Crandall, Philip G.; Engler, Robert K.; Beck, Dennis E.; Killian, Susan A.; O'Bryan, Corliss A.; Jarvis, Nathan; Clausen, Ed
Abstract One of the most pressing issues for many land grant institutions is the ever increasing cost to build and operate wet chemistry laboratories. A partial solution is to develop computer‐based teaching modules that take advantage of animation, web‐based or off‐campus learning experiences directed at engaging students' creative experiences. We used the learning objectives of one of the most difficult topics in food chemistry, enzyme kinetics, to test this concept. Students are apprehensive of this subject and often criticize the staid instructional methods typically used in teaching this material. As a result, students do not acquire a useful background in this important subject. To rectify these issues, we developed an interactive augmented reality application to teach the basic concepts of enzyme kinetics in the context of an interactive search that took students to several locations on campus where they were able to gather raw materials and view videos that taught the basics of enzyme kinetics as applied to the production of high fructose corn syrup (HFCS). The students needed this background to prepare for a mock interview with an HFCS manufacturer. Students and instructors alike found the game to be preferable to sitting in a classroom listening to, or giving, a PowerPoint presentation. We feel that this use of gaming technology to teach difficult, abstract concepts may be a breakthrough in food science education and help alleviate the drain on administrative budgets from multiple wet labs.